Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1103/physrevlett.79.2795
|View full text |Cite
|
Sign up to set email alerts
|

Pinning Control of Spatiotemporal Chaos

Abstract: Linear control theory is used to develop an improved localized control scheme for spatially extended chaotic systems, which is applied to a coupled map lattice as an example. The optimal arrangement of the control sites is shown to depend on the symmetry properties of the system, while their minimal density depends on the strength of noise in the system. The method is shown to work in any region of parameter space and requires a significantly smaller number of controllers compared to the method proposed earlie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
182
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(187 citation statements)
references
References 16 publications
1
182
0
4
Order By: Relevance
“…Lattices are structured regular networks in which all the nodes have the same degree (also termed as the coordination number z) and are widely used in physics to describe phenomena that take place in ordered extended systems. For example, pinning control of coupled map lattices has been studied in [16,17].…”
Section: Linear and Square Latticesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lattices are structured regular networks in which all the nodes have the same degree (also termed as the coordination number z) and are widely used in physics to describe phenomena that take place in ordered extended systems. For example, pinning control of coupled map lattices has been studied in [16,17].…”
Section: Linear and Square Latticesmentioning
confidence: 99%
“…In pinning control schemes [16,17,18,19], some nodes are permanently selected (pinned) to be the network controllers. Specifically, these nodes, referred to as reference sites or pinned sites, play the role of network leaders/pacemakers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, the study on controlling the dynamics of a network and guiding it to a desired state, such as, an equilibrium point or a periodic orbit of the network has become an interesting and important direction in this research field. 7,[18][19][20][22][23][24]26,27 It has been revealed that, in the process of controlling various networks, feedback control serves as a simple and effective approach for stabilization and synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the control cost, some feedback injections may be added to a fraction of network nodes, which is known as pinning control. [17][18][19][20][22][23][24]26,27,33 In Ref. 17, pinning control of spatiotemporal chaos was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive future prospect is to control such modes by exploiting their quantized nature and their sensitivity to boundary conditions. An alternative approach might be to eliminate alternans using multiple dispersed controllers spaced at distances less than the maximum controllable tissue distance [dispersed controller approaches have been used to control spatiotemporal dynamics in physical systems [24][25][26], and in simulated cardiac monolayers for the control of spiral-wave reentry or fibrillation [16,27] ].…”
mentioning
confidence: 99%